Effect of laser shock peening on inconel 718 for hydrogen embrittlement - Mahesh, Aditya (Nanyang Technological University, 2024)
This study investigates the effects of Laser Shock Peening on Inconel 718 for hydrogen embrittlement. Cylindrical dog bone samples of Inconel 718 were made by forging and machining (milling). The resultant dog bone samples were subjected to Laser Shock Peening at the Advanced Remanufacturing and Technology Centre with a set of process parameters, with a focus on pulse energy, pulse width, and peak power density. Cathodic hydrogen charging was performed on the samples, and they were analyzed using an Olympus digital microscope. Vicker’s hardness testing was performed on the samples to determine the mechanical properties of the samples before and after laser shock peening. The study shows that the hardness values of the laser shock peened samples are higher than those of non-laser shock peened samples, indicating improved performance of laser shock peening. Slow strain rate tensile tests were also conducted on multiple samples (laser shock peened and hydrogen charged), and it was noticed that hydrogen diffusion into the dog bone samples decreased the tensile strength of the superalloy. This project also provided some insights regarding the diffusion of hydrogen into the superalloys and how laser shock peening could be considered as one of the ideal industrial solutions to improve the mechanical properties of superalloys, thereby reducing wastage, which in turn saves huge amounts of money.